Analisis Yuridis Fenomena Blind Box Sebagai Bentuk Perjudian Digital Berdasarkan Undang-Undang Nomor 1 Tahun 2024 Tentang Informasi Dan Transaksi Elektronik - Astrawan, I Kadek Angga Budi; Darma, I Made Wirya (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
Article 27 paragraph (2) of Law Number 1 of 2024 concerning Electronic Information and Transactions (ITE Law) contains a prohibition against any person who intentionally and without rights distributes or makes accessible electronic information that has “gambling content.” However, this phrase lacks a clear interpretation or definition, resulting in legal uncertainty in its application. This study aims to analyze the legal implications of the absence of a clear interpretation and its impact on law enforcement practices in the cyber realm. Using a normative juridical approach and conceptual analysis, this study finds that the absence of an explicit definition leads to differences in interpretation among law enforcement officials, potentially resulting in the over- criminalization of digital businesses and hindering consumer protection from covert gambling practices in the virtual world. In addition, the ambiguity of this phrase has resulted in weak law enforcement, as authorities find it difficult to prove the element of gambling in digital activities such as loot boxes, blind boxes, or luck-based lottery systems that are often used in online applications and games. As a result, the principles of legal certainty and justice as stipulated in Article 28D paragraph (1) of the 1945 Constitution have been neglected. This study emphasizes the need to establish implementing regulations or official guidelines that explain the objective indicators of “gambling content” in the digital space, including elements of economic value, dependence on luck, and potential financial gains. With the clarity of these norms, it is hoped that there will be uniformity in law enforcement, increased consumer protection, and the creation of fair legal certainty in the digital age.